PENGARUH PENANAMAN MODAL DALAM NEGERI, PENANAMAN MODAL ASING, DAN PENGELUARAN PEMERINTAH TERHADAP PRODUK DOMESTIK REGIONAL BRUTO KABUPATEN BERAU - Tamam (ECO-BUILD, 2025)
The purpose of this study is, among others, to find out and analyze the Influence of Domestic Investment, Foreign Investment, and Government Expenditure on the Gross Regional Domestic Product of Berau Regency. The data used are secondary data for the 2015-2023 period in the form of PMA and PMDN data obtained from the DPMPTSP of East Kalimantan Province, and Government Expenditure obtained from BPKAD Berau Regency and GDP data obtained from BPS Berau Regency. The analysis method used is multiple linear regression using the SPSS program. The results of this study show that simultaneously investment consisting of FDI, PMDN, and Government Expenditure has a significant effect on GDP. While partially PMA and Government Expenditure have a positive but not significant effect on GDP, PMDN has a positive and significant effect on GDP.